World Wide Tourism: A Review - Chavan, Rajashri Ramesh; Bhola, Sarang Shankar (Indian Journal of Marketing, 2014)
The present study presents a detailed review of papers published on tourism from across the world. We referred to a number of studies to check the impact of tourism, tourism policies and governance, analyzed techniques in tourism research, examined concepts of tourism, demand indicators, and many others. The purpose of the present study is to highlight the way developed and developing countries probe into tourism subjects and market their destinations. The present paper, with respect to worldwide tourism development, starts with analyzing the existing tourism situation, followed by tourism product development with a new approach. The next step is to measure the effects of tourism on the local economy as well as on the other sectors. For strategic decision-making, focus needs to be placed on statistical tools, which could be used for qualitative analysis in the tourism industry. After that, the focus of the study shifts to the importance of tourism in handling social issues. Next, the paper discusses the psychology of the consumers and the level of quality tourism services expected by them. The present paper could be utilized as a guideline for tourism development in a developing nation like India. In India, tourism development is in a nascent stage, where we are looking at basic tourist infrastructural facilities, where as in the developed countries, they look at the psychographic profiles of the tourists. Development of newer tourism products and management profiles of such products need to be designed.